Wali and Karama: A Discourse and Authority Contestation in al-Tarmasi’s Bughyat al-Adhkiya’ - Ade Fakih Kurniawan; Noorhaidi Hasan; Achmad Zainal Arifin (Al-Jami'ah: Journal of Islamic Studies, 2019)
This paper aims to analyze Muhammad Mahfūẓ al-Tarmasī’s concept of wali and karāma, as well as his response and position in the discourse on those issues. Drawing on historical, hermeneutics, and intertextual approach, it will elaborate his involvement in the 19th century discourse on wali and karāma, in which the Wahhabiyya’s strong influence in Mecca was taking place. In this sense, Mahfūẓ wrote a treatise on Sufism entitled Bughyat al-Adhkiyā’ fī Bahthi’an Karāmāt al-Awliyā’. Although he mastered on tasawwuf and possessed a genealogical chain to al-Ghazali, al-Qushairi and some other Sufis, he did not use their arguments. He preferred to quote the arguments of the jurists (fuqahā’), such as al-Subkī and al-Haytamī. This actually shows the strength of his work in compiling arguments using the “criticism from within” approach. He realized, to some extent, that criticism to Sufism mainly came from the jurists (fuqahā’). Therefore, in order to be easily accepted, criticizing critics needs to employ the same perspective, fuqahā’s arguments. In fact, Mahfūẓ criticism was not only directed at the jurists (fuqahā’) but also to the group which at that time were incessantly spreading the ideas delegitimizing Sufism (in the context of orthodoxy), Wahhabiyya. This can be seen clearly in the way of Mahfūẓ’s selection of figures and groups to whom he criticized. But interestingly, he delivered critics in a smooth way and did not show his finger directly to the nose of Wahhabiyya.[Tulisan ini merupakan analisis terhadap konsep wali dan karomah menurut Muhammad Mahfūẓ al-Tarmasi, serta respon dan posisinya dalam diskursus isu-isu tersebut. Dengan menggunakan pendekatan historis, hermeneutika, dan intertekstual, tulisan ini menjelaskan keterlibatannya dalam wacana abad 19 tentang wali dan karomah, di mana pengaruh kuat Wahhabiyya di Mekah tengah berlangsung. Untuk itu, Mahfūẓ menulis sebuah risalah tentang Sufisme berjudul Bughyat al-Adhkiyā’ fi Bahthi’an Karāmat al-Awliyā’. Meski ia menguasai tasawwuf dan memiliki silsilah spiritual yang sampai kepada beberapa Sufi kenamaan, namun dalam karyanya ini ia tidak menggunakan argumen-argumen mereka. Ia lebih suka mengutip argumen para ahli hukum (fuqahā’), seperti al-Subki dan al-Haytami. Ini merupakan salah satu kekuatan dari kepiawaiannya dalam menyusun argumen menggunakan pendekatan “critic from within” karena ia menyadari bahwa kritik terhadap tasawuf labih banyak berasal dari para fuqahā’. Oleh karena itu, agar mudah diterima, suatu kritik perlu menggunakan perspektif yang sama dengan sang pengkritik, dalam hal ini argumen fuqaha. Faktanya, kritik Mahfūẓ tidak hanya diarahkan pada para fuqahā’ tetapi juga kepada kelompok yang pada saat itu terus-menerus menyebarkan ide-ide delegitimasi tasawuf (dalam konteks ortodoksi), seperti Wahhabiyya. Ini dapat dilihat dengan jelas dari cara Mahfūẓ memilih tokoh dan kelompok yang ia kritik. Namun yang menarik, ia menyampaikan kritik dengan cara yang halus dan tidak secara explisit menunjuk langsung Wahhabiyya yang saat itu mulai berkuasa.]